Multiple and frequent trypanosomatid co-infections of insects: the Cuban case study - Jan Votýpka; Šimon Zeman; Eva Stříbrná; Petr Pajer; Oldřich Bartoš; Petr Kment; Julius Lukeš; Julius Lukeš (Parasitology, 2024)
Trypanosomatids are obligate parasites of animals, predominantly insects and vertebrates, and flowering plants. Monoxenous species, representing the vast majority of trypanosomatid diversity, develop in a single host, whereas dixenous species cycle between two hosts, of which primarily insect serves as a vector. To explore in-depth the diversity of insect trypanosomatids including their co-infections, sequence profiling of their 18S rRNA gene was used for true bugs (Hemiptera; 18% infection rate) and flies (Diptera; 10%) in Cuba. Out of 48 species (molecular operational taxonomic units) belonging to the genera Vickermania (16 spp.), Blastocrithidia (7), Obscuromonas (4), Phytomonas (5), Leptomonas/Crithidia (5), Herpetomonas (5), Wallacemonas (2), Kentomonas (1), Angomonas (1) and two unnamed genera (1 + 1), 38 species have been encountered for the first time. The detected Wallacemonas and Angomonas species constitute the most basal lineages of their respective genera, while Vickermania emerged as the most diverse group. The finding of Leptomonas seymouri, which is known to rarely infect humans, confirms that Dysdercus bugs are its natural hosts. A clear association of Phytomonas with the heteropteran family Pentatomidae hints at its narrow host association with the insect rather than plant hosts. With a focus on multiple infections of a single fly host, using deep Nanopore sequencing of 18S rRNA, we have identified co-infections with up to 8 trypanosomatid species. The fly midgut was usually occupied by several Vickermania species, while Herpetomonas and/or Kentomonas species prevailed in the hindgut. Metabarcoding was instrumental for analysing extensive co-infections and also allowed the identification of trypanosomatid lineages and genera.